Retropharyngeal approach in cervical disc hernias - Oral, Şükrü (Journal of Surgery and Medicine, 2020)
Aim: High-level disc hernias are rare pathologies encountered in clinical practice. Treatment is more difficult than other cervical disc hernias. In this study, we aimed to convey our clinical experience in C2-3 and C3-4 disc herniations, also presenting the complications we encountered during surgical treatment. Methods: In this retrospective cohort study, we reviewed the clinical and radiological records of 42 patients we operated between 2010-2019. Magnetic resonance imaging, computed tomography and direct radiographs were utilized as imaging modalities. Anterior retropharyngeal approach was the preferred surgical method. The modified Japanese Orthopedic Association (mJOA) score and Nurick Scale were used in clinical follow-up and physical examination of these patients. Results: Among all patients, the most common symptom was severe pain radiating from the neck to the occipital region. The mean age was 54.14 years. The average mJOA scores were 15.1 in the preoperative period and 17 in the postoperative sixth month. We observed that 83.3% of our patients had an mJOA recovery rate of fifty percent and above. All but seven patients’ complaints improved well after treatment. There was a negative correlation between symptom duration and recovery rate (P=0.003, Correlation Coefficient r=-0.449). The rate of recovery was lower in patients with a longer duration of symptoms. Three of our patients developed difficulty in swallowing after the operation and recovered within four weeks with diet and exercise. Conclusion: We determined that retropharyngeal approach is a safe option for disc hernias at the upper cervical level. However, long operation time and excessive retraction during surgery may lead to complications such as difficulty in swallowing due to the stretching of the neural structures.